1987
DOI: 10.1159/000146468
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anatomic Metric Values of the Foramen Magnum and Its Relation to Sex

Abstract: The sagittal and transverse diameters of the foramen magnum were examined in 100 human skulls (74 male, 26 female).The results were statistically analyzed and compared with those obtained by other authors. Our findings show that the sagittal and transverse diameters are clearly different, as well as the total area of the foramen magnum, these parameters being larger in male skulls than in female.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 1 publication
5
33
0
Order By: Relevance
“…Nevertheless, both diameters are slightly smaller in females than in males as already stated by Olivier (1975). Our values for each sex are generally similar to those measured by Catalina-Herrera (1987). The lack of a significant sexual dimorphism in foramen magnum size-as found in the current study-is consistent with earlier reports showing an absence of larger male vertebral canal dimensions (Eisenstein, 1977;Porter et al, 1978;Hasue et al, 1983;Kikuchi et al, 1984).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, both diameters are slightly smaller in females than in males as already stated by Olivier (1975). Our values for each sex are generally similar to those measured by Catalina-Herrera (1987). The lack of a significant sexual dimorphism in foramen magnum size-as found in the current study-is consistent with earlier reports showing an absence of larger male vertebral canal dimensions (Eisenstein, 1977;Porter et al, 1978;Hasue et al, 1983;Kikuchi et al, 1984).…”
Section: Discussionsupporting
confidence: 92%
“…The foramen magnum, as a transition zone between spine and skull, plays an important role as a landmark because of its close relationship to key structures such as the brain and the spinal cord. There is a small heterogeneous group of anthropological and medical papers focusing on the foramen magnum: simple morphometric analysis of foramen magnum dimensions (Sendemir et al, 1994), foramen magnum size as a part of human occipital bone biometry (Olivier, 1975), its size relative to sex (Catalina-Herrera, 1987;Uysal et al, 2005), its relationship to the intra-cranial volume (Acer et al, 2006), its relationship to stature (Röthig, 1971), the use of the foramen magnum as an identification mark for fire victims (Holland, 1989), the inter-and intra-variability of the foramen magnum position in different species (Ahern, 2005), foramen magnum-carotid foramina relationship as a probable species diagnostic mark (Schaeffer, 1999), and the foramen magnum region in relation to surgical approaches (Muthukumar et al, 2005).Despite its anatomical and clinical relevance, there is still a lack of basic osteometric studies. Furthermore, to the best of our knowledge, no study has ever…”
mentioning
confidence: 99%
“…Previous studies have reported that the dimensions of the foramen magnum (Teixeira, 1982;Holland, 1986;Catalina-Herrera, 1987;Gü nay and Altinkök, 2000;Uysal et al, 2005, Gapert et al, 2009b, and occipital condyles (Holland, 1986;Uysal et al, 2005;Gapert et al, 2009a) are sexually dimorphic in adults, with up to of 90% accuracy for sex determination. The goal of this article is to examine if significant differences in dimensions of the foramen magnum and occipital condyles exist between male and female juveniles, and if these dimensions can be used to reliably estimate sex.…”
Section: Ontogeny Of the Basioccipitalmentioning
confidence: 98%
“…Catalina-Herrera (1987) indicated that the sagittal and transverse dimensions of the foramen magnum were significantly higher in men's skulls. Zaidi & Dayal (1988) classified a sample of Indian skulls according to the shape and dimensions of the foramen magnum, reporting differences between the skulls of male and female, which was similar to the findings of Henríquez-Pino et al (1995) in the Brazilian skulls.…”
Section: Introductionmentioning
confidence: 95%